Pengembangan Buku Saku Ekonomi Dengan Konsep Mind Mapping Untuk Meningkatkan Motivasi Belajar Peserta Didik - Fines Anita Putri Premianti (Universitas Negeri Surabaya, 2021)
Based on the students' low motivation to learn economics, this study seeks to develop an economics pocketbook. Using the ADDIE method, this development research (R&D) aims to increase students' motivation to learn economics and to determine the level of feasibility, practicality, and effectiveness of using pocketbooks. Data were collected by observing, interviewing, and giving questionnaires. Measurement of learning motivation was carried out before and after giving the economic pocketbook using a questionnaire. It is also used to determine the practicality and effectiveness of using pocketbooks. The data were analyzed descriptively quantitatively in order to obtain a description of the feasibility of the material, media, graphics, as well as student responses and changes in participants' learning motivation. The results of the feasibility assessment show a very feasible category with a validation percentage of 90.6% from material experts; 93.3% of media experts; and 84% of graphic experts. In addition, participants revealed that pocketbooks were considered practical and able to increase students' motivation to learn economics by 3.9% with a t-test result of 0,01.